European Non-Polio Enterovirus Network: Introduction of Hospital-Based Surveillance Network to Understand the True Disease Burden of Non-Polio Enterovirus and Parechovirus Infections in Europe - Heli Harvala; Kimberley S. M. Benschop; Natasa Berginc; Sofie Midgley; Katja Wolthers; Peter Simmonds; Susan Feeney; Jean-Luc Bailly; Audrey Mirand; Thea K. Fischer; on behalf of the ENPEN Hospital-Based Surveillance Network (Microorganisms, 2021)
Background. Non-polio enteroviruses (EVs) and human parechoviruses (PeVs) cause a wide range of human infections. Limited data on their true disease burden exist as standardized European-wide surveillance is lacking. Aims. Our aim is to estimate the disease burden of EV and PeV infections in Europe via establishment of standardized surveillance for hand, foot and mouth disease (HFMD) and respiratory and neurological infections caused by these viruses. We will also assess the sensitivity of assays implemented in the network of participating laboratories so that all EV and PeV types are adequately detected. Plan. The European Non-Polio Enterovirus Network (ENPEN) has developed standardized protocols for a prospective, multi-center and cross-sectional hospital-based pilot study. Protocols include guidance for diagnosis, case definition, detection, characterization and reporting of EV and PeV infections associated with HFMD and respiratory and neurological diseases. Over 30 sites from 17 European countries have already registered to this one pilot study, likely to be commenced in 2022. Benefits. This surveillance will allow European-wide comparison of data on EV and PeV infection. These data will also be used to determine the burden of EV and PeV infections, which is needed to guide the further prevention measures and policies.